2002
DOI: 10.1007/s11746-002-0429-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐catalyzed esterification of stearic acid with ethanol, and hydrolysis of ethyl stearate, near the critical point in supercritical carbon dioxide

Abstract: The effect of pressure on the lipase-catalyzed reaction in supercritical carbon dioxide (SCCO 2 ) was investigated for the esterification of stearic acid (SA) with ethanol and the hydrolysis of ethyl stearate (ES) near the critical point, ranging from 6 to 20 MPa in pressure and 35 to 60°C in temperature. The esterification rate of SA began to increase near the critical point and kept increasing steadily with an increase in pressure, reflecting the increase in SA solubility in SCCO 2 . The hydrolysis rate of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Similar results for thermal behaviour of Lipozyme RM IM have been reported in the literature for the synthesis of n-octyl oleate in SC-CO 2[16]. Conversion around 80 % was observed in the range 308 15. 333.15 K at 10 MPa, whereas higher temperatures (343.15 and 353.15 K)led to lower conversion (around 65 %) yet slightly higher initial reaction rates, which may indicate that thermal deactivation is not immediate.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Similar results for thermal behaviour of Lipozyme RM IM have been reported in the literature for the synthesis of n-octyl oleate in SC-CO 2[16]. Conversion around 80 % was observed in the range 308 15. 333.15 K at 10 MPa, whereas higher temperatures (343.15 and 353.15 K)led to lower conversion (around 65 %) yet slightly higher initial reaction rates, which may indicate that thermal deactivation is not immediate.…”
supporting
confidence: 87%
“…Different results have been found in the literature regarding the effect of pressure on Lipozyme RM IM-catalyzed reactions in SC-CO 2 . For instance, in the study of esterification of stearic acid with ethanol catalyzed by Lipozyme IM in SC-CO 2 in the range from 6 to 20 MPa at 323.15 K, Nakaya et al [15] found an increase in esterification rate with an increase in pressure, but a maximum was found in the hydrolysis rate of the corresponding ethyl stearate. Laudani et al [16] performed a detailed kinetic and thermodynamic study of the esterification of oleic acid with 1-octanol catalyzed by Lipozyme RM IM in dense carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Both chemical (e.g., acid) and enzymatic (e.g., lipases) approaches have been developed to be efficient for the hydrolysis of triglycerides, which are the major component of oils and fats . In view of the enzyme specificity and high mass transfer rate of Sc‐CO 2 , oils or fats dissolved in Sc‐CO 2 would be favorable for enzymatic hydrolysis, as well as product separation by simple reduction of the system pressure . Numerous lipases are known to be active in Sc‐CO 2 , including for the hydrolysis of bio‐esters .…”
Section: Co2‐enabled Depolymerization Of Biomass Feedstocksmentioning
confidence: 99%
“…[149,150] In view of the enzyme specificity and high mass transfer rate of Sc-CO 2 ,o ils or fats dissolved in Sc-CO 2 would be favorable for enzymatic hydrolysis, as well as product separation by simple reduction of the system pressure. [151][152][153] Numerousl ipases are known to be active in Sc-CO 2 ,i ncluding for the hydrolysis of bio-esters. [154,155] However,t he moisture content directly affects the lipase catalytic activity,w hereby sufficient water is typically required to make lipasesb ehavea se fficient biocatalysts.…”
Section: Co 2 -Enabled Hydrolysis Of Bio-estersmentioning
confidence: 99%
“…An interesting study has been performed with lipase-catalyzed esterification of stearic acid with ethanol, and subsequent hydrolysis of ethyl stearate under the conditions set near to the critical point in supercritical carbon dioxide (p = 6 to 20 MPa, t = 35 to 60 °C) [ 166 ], resulting in an observation of the esterification rate of stearic acid increasing near the critical point and keeping the increase steady with increasing the pressure, and reflecting the increasing solubility of stearic acid in supercritical medium. The hydrolysis rate of ethyl stearate showed its maximum at a pressure near the critical point, and it was dependent on the initial concentration of ethyl stearate in the system.…”
Section: Enzymes Acting In Lipid Modificationsmentioning
confidence: 99%